2020
DOI: 10.3390/met10040504
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical Effects of Niobium in Dual Phase Steel

Abstract: Dual phase (DP) steels are widely applied in today’s automotive body design. The favorable combination of strength and ductility in such steels is in first place related to the share of ferrite and martensite. The pronounced work hardening behavior prevents localized thinning and allows excellent stretch forming. Niobium microalloying was originally introduced to dual phase steel for improving bendability by refining the microstructure. More recently developed “high ductility” (HD) DP steel variants provide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The manuscripts gathered in this Special Issue are committed to a variety of steel grades, embracing DP (Dual Phase) steels [1], medium-Mn steels [2,3], CFB (Carbide Free Bainitic steels) [4], nano-bainitic cast steel [5], δ-TRIP (TRansformation Induced Plasticity) [6] and precipitation hardened ferritic stainless steel [7].…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The manuscripts gathered in this Special Issue are committed to a variety of steel grades, embracing DP (Dual Phase) steels [1], medium-Mn steels [2,3], CFB (Carbide Free Bainitic steels) [4], nano-bainitic cast steel [5], δ-TRIP (TRansformation Induced Plasticity) [6] and precipitation hardened ferritic stainless steel [7].…”
Section: Contributionsmentioning
confidence: 99%
“…A wide range of topics are researched that comprise the alloy design [2,6,7], optimization of both the hot working process [2] and the final heat treatment [5], and the final mechanical properties [1,3,4,6].…”
Section: Contributionsmentioning
confidence: 99%
“…Systematic alloy variations in laboratory trials have indicated that the tensile strength of grey cast iron can be most efficiently increased by simultaneously refining the eutectic cell size and the pearlite interlamellar spacing (see Fig. 4) [21]. In that respect, the combined alloying of molybdenum and niobium has a particularly high strengthening potential.…”
Section: Grey Cast Ironsmentioning
confidence: 99%
“…Hypo-and hyper-eutectic alloy concepts of grey cast iron grades and specified mechanical properties according to European automotive standards Effect of niobium addition on microstructural refinement in grey cast iron[18] Effect of microstructural refinement on tensile strength in grey cast iron based on laboratory results provided by Shanghai University[21] …”
mentioning
confidence: 99%
“…More and more researchers add microalloying elements such as Nb, Ti, and V to develop new materials. [ 15–17 ] Cai et al obtained ultra‐low carbon Ti–Mo–Nb steel with high yield strength (YS) by introducing nano‐precipitates, with a precipitation strengthening of 210 MPa and a YS of 634 MPa. [ 18 ] Chen et al improved the YS of hot‐formed steel by 145.6–263.4 MPa by introducing the precipitates (Nb, V, Ti)C. [ 19 ] However, the strengthening mechanism of multiphase steels treated by the Q–P process for low‐carbon microalloyed high‐strength steels is rarely studied.…”
Section: Introductionmentioning
confidence: 99%